Effect of Monetary Policy and Financial Development on Foreign Direct Investment Inflow in Nigeria - Egbetunde, Tajudeen; Abayomi, Muftau Adesina (Acta Universitatis Danubius. Œconomica, 2024)
The study investigates effect of monetary policy and financial development on Foreign Direct Investment (FDI) inflow in Nigeria. Prior Work: The existing literature shows that nexus between monetary policy, financial development and FDI inflow remains bone of contention and this study provides empirical evidence in Nigeria for appropriate policy formulation. Approach: The study uses ARDL econometric technique. Results: The results show that monetary policy and financial development had long run influence on FDI inflow in Nigeria; and further show that in the long run monetary policy had significant and positive influence on FDI inflow, but had significant and negative influence in the short run. Likewise, financial development had long run positive and significant impact on FDI inflow, but had significant and negative effect in the short run. The study concludes that monetary policy and financial development play a pivotal and substantial role in attracting FDI inflow in Nigeria. Implication: The study recommends that monetary authority in the country should put in place appropriate macroeconomic mechanism, efficient monetary policy and strong financial institutions that will attract more FDI inflows into the country. Value: The study establishes causal effect of monetary policy and financial development on FDI inflow in Nigeria.